A profile of primary school students’ literacy through EMI in CLIL Contexts - Rachmajanti, Sri; Anugerahwati , Mirjam; Unsiah, Frida (Universitas Muhammadiyah Sidoarjo, 2023)
For several years, the competence of students in Indonesia has always been recorded as very low. In PISA, Indonesia ranks at the 3rd or 4th lowest position, especially in Reading, Mathematics, and Science. This condition has, of course, raised the concerns of educators in Indonesia, and some schools then decided to implement an international curriculum along with the 2013 Curriculum. With the international curriculum, students are required to have very good literacy, to comprehend the texts and questions they work on. This also entails teaching them with teaching strategies which, besides developing their language competence, also enhance their critical thinking skills. This paper reports some ways in which EMI and CLIL can develop primary school students‟ English proficiency, literacy, and critical thinking skills. Data were taken from some Primary Schools which implement the synergy of national and international standard curricula, particularly from the scores of the students on two tests. Focus of the learning is given to the students’ English proficiency and literacy. The total numbers are 248 students from 14 primary schools located in most cities in East Java and some in South Celebes. The results show that the program equips the student with higher proficiency, literacy, and critical thinking skills. This study implies that EMI in CLIL context can accommodate primary school students’ literacy learning. HIGHLIGHTS : ESL lessons in Primary schools implement the synergy of the National Curriculum and international framework do enhance students‟ literacy, proficiency, and critical thinking skills. The implementation of CLIL and EMI in primary school evidently gives benefits to the students‟ language proficiency. It is confidently stated that EMI, which is implemented in the CLIL program, particularly in the primary schools which implement the synergy of dual curriculum (the 2013 Curriculum and the international framework).